2017
DOI: 10.1177/0271678x17724682
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting statin for aneurysmal subarachnoid hemorrhage: A randomized, double-blind, placebo-controlled trial

Abstract: Statins have pleiotropic effects that are considered beneficial in preventing cerebral vasospasm and delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage (aSAH). Many studies using statins have been performed but failed to show remarkable effects. We hypothesized that a long-acting statin would be more effective, due to a longer half-life and stronger pleiotropic effects. Patients with aSAH were randomly assigned to a pitavastatin group (4 mg daily; n = 54) and a placebo group ( n = 54) after rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 55 publications
0
44
0
2
Order By: Relevance
“…The literature search strategy yielded a total of 18 studies for analysis, which comprised of randomized controlled trials (RCTs) [16,17,19,20,[36][37][38][39][40][41][42][43], prospective observational cohort studies [15,44] and retrospective observational studies [18,[45][46][47]. This represented 2594 patients.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search strategy yielded a total of 18 studies for analysis, which comprised of randomized controlled trials (RCTs) [16,17,19,20,[36][37][38][39][40][41][42][43], prospective observational cohort studies [15,44] and retrospective observational studies [18,[45][46][47]. This represented 2594 patients.…”
Section: Search Resultsmentioning
confidence: 99%
“…If bias was not addressed in the trials, we assumed an unclear risk. Nine studies (50.0%) were randomized control trials, with blinding of participants and personnel [16,17,19,20,36,38,40,41,43]. Risk of overall bias was considered high in 7 studies (39.0%) [15,37,39,42,[44][45][46], whereas the risk was minimal in 8 studies (44.4%) [16,17,19,20,36,38,40,41].…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, randomized controlled phase II studies have demonstrated that acute administration of statin directly after SAH decreased the incidence of radiological vasospasm, and reduced the clinical signs of delayed ischaemic neurological deficits and mortality . However, some experimental and clinical studies demonstrated the different or even contradictory results . Thus, further well‐designed multicentre randomized controlled trials are required.…”
Section: The Pathophysiology Of Sahmentioning
confidence: 99%
“…A variety of managements can help patients with ASH, including statin, clazosentan, cilostazol, simvastatin, diltiazem, simvastatin, methylprednisolone, rehabilitation, and fasudil, [1123] especially for fasudil. Although several studies have reported that fasudil can be utilized for ASH treatment effectively, [2023] its conclusion is still unconfirmed.…”
Section: Introductionmentioning
confidence: 99%